Respuesta :
Answer:
X = 1
Step-by-step explanation:
To solve the system of equation by susbtitution:
3x + y = 9
y = –4x + 10
We can follow the steps thus:
Substitute the value of y in the first equation:
As in the second equation y = -4x + 10 we can substitute in the first equation as follows:
3x + y = 9
3x + -4x + 10 = 9
Combine like terms:
3x + -4x + 10 = 9
Like therms are the therms with X (3x - 4x = -1x):
-1x + 10 = 9
Apply the subtraction property of equality:
-1x + 10 = 9
As 10 is suming, it passes to subtracting the 9:
-1x = 9 - 10
-1x = -1
Apply the division property of equality:
-1x = -1
Dividing in -1:
x = -1 / -1
X = 1
Answer:
b
Step-by-step explanation:
The value of x in this system of equations is 1.
3x + y = 9
y = –4x + 10
Substitute the value of y in the first equation:
Combine like terms:
Apply the subtraction property of equality:
Apply the division property of equality:
3x + (–4x + 10) = 9
–x + 10 = 9
–x = –1
x = 1
What is the value of y?
y =